Relatório Final da Prática de Ensino Supervisionada Desenvolvendo a Oralidade no Jardim de Infância - Gouveia, Ana Teresa; Ferreira, Ana (2015)
The present report of the supervised practice of teaching that is presented here reflects all the work carried out along an academic year in a college. In this report, will be presented some characterizations of the institution, of the classroom, of the group of children where we were inserted during the internship, which correspond to the first phase of our internship being this the observation. The second phase of our internship was characterized for being interventional, having as objective to pay attention to the necessities of the children in the group and to answer to their needs. In the initial characterization it was possible to verify a problem: the orality of the children in the group. Thus, it was defined as a guiding theme to develop the following theme: Developing Orality in Kindergarten. When the priority area was chosen, we proceed to the selection of some objectives to be developed along the practice: -Enrich the vocabulary -Oral expression -Develop the ability to listen and be attentive -Develop the free and spontaneous communication -Retell stories through images We proceed to the bibliographical search to review the concepts and adapt the intervention to the necessities and characteristics of the children of the group. Were thus implemented activities aimed at achieving the goals initially set. In the end of the internship the children of the group were much more communicative, expressing themselves more clearly and communicating spontaneously with adults and their peers.